(-8x+2y)(-4x+4y)=

Simple and best practice solution for (-8x+2y)(-4x+4y)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-8x+2y)(-4x+4y)= equation:


Simplifying
(-8x + 2y)(-4x + 4y) = 0

Multiply (-8x + 2y) * (-4x + 4y)
(-8x * (-4x + 4y) + 2y * (-4x + 4y)) = 0
((-4x * -8x + 4y * -8x) + 2y * (-4x + 4y)) = 0

Reorder the terms:
((-32xy + 32x2) + 2y * (-4x + 4y)) = 0
((-32xy + 32x2) + 2y * (-4x + 4y)) = 0
(-32xy + 32x2 + (-4x * 2y + 4y * 2y)) = 0
(-32xy + 32x2 + (-8xy + 8y2)) = 0

Reorder the terms:
(-32xy + -8xy + 32x2 + 8y2) = 0

Combine like terms: -32xy + -8xy = -40xy
(-40xy + 32x2 + 8y2) = 0

Solving
-40xy + 32x2 + 8y2 = 0

Solving for variable 'x'.

Factor out the Greatest Common Factor (GCF), '8'.
8(-5xy + 4x2 + y2) = 0

Factor a trinomial.
8((x + -1y)(4x + -1y)) = 0

Ignore the factor 8.

Subproblem 1

Set the factor '(x + -1y)' equal to zero and attempt to solve: Simplifying x + -1y = 0 Solving x + -1y = 0 Move all terms containing x to the left, all other terms to the right. Add 'y' to each side of the equation. x + -1y + y = 0 + y Combine like terms: -1y + y = 0 x + 0 = 0 + y x = 0 + y Remove the zero: x = y Simplifying x = y

Subproblem 2

Set the factor '(4x + -1y)' equal to zero and attempt to solve: Simplifying 4x + -1y = 0 Solving 4x + -1y = 0 Move all terms containing x to the left, all other terms to the right. Add 'y' to each side of the equation. 4x + -1y + y = 0 + y Combine like terms: -1y + y = 0 4x + 0 = 0 + y 4x = 0 + y Remove the zero: 4x = y Divide each side by '4'. x = 0.25y Simplifying x = 0.25y

Solution

x = {y, 0.25y}

See similar equations:

| c=(3x+y-4)*5-5y+3 | | 5-15t=-15t-14 | | 4+14x=2x-8+12x | | -18n+6n-3=5-12n | | 965.3616=87.92*r^2+62.17*r | | -6y-1=-9y+2 | | 7x-5+3x=75 | | -6-10v=-10v-6 | | w^2-2w=-67 | | -4m+7=7-4m | | 3(p-3)=24 | | -3z-10=-z+10 | | -8r-9=-8r | | 2(x-3)+5(1-x)=2 | | 11m-66-17= | | 5k-9=-9+5k | | 40(9+7x)+3-5x=17 | | 965.3616=87.92*r^2+6.28*r*9.9 | | 2-2u=-2u+2 | | -2x+-1+x= | | 8(j-4)=2(4j-3) | | 0=5b-5b | | 5(5a+2)-4a=0 | | 6x-10=5x-11 | | -2p=-p+6 | | 8(j-4)=3(4j-16) | | 5t-45= | | 0=6s-6s | | 965.3616=6.28*14*r^2+6.28*r*9.9 | | 4x^4+12x=0 | | 0=10d-10d | | 7s+11= |

Equations solver categories